2018
DOI: 10.1007/s00784-018-2750-1
|View full text |Cite
|
Sign up to set email alerts
|

Split-mouth evaluation of connective tissue graft with or without enamel matrix derivative for the treatment of isolated gingival recession defects in dogs

Abstract: Objectives The potential additive effect of an enamel matrix derivative (EMD) to a subepithelial connective tissue graft (CTG) for recession coverage is still controversially discussed. Therefore, the aim of this study was to histologically evaluate the healing of gingival recessions treated with coronally advanced flap (CAF) and CTG with or without EMD in dogs. Materials and methods Gingival recession defects (5 mm wide and 7 mm deep) were surgically created on the labial side of bilateral maxillary canines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The amounts of STT in the CAF/HA group were comparable to that in the CAF group, without statistically significant differences. On the other hand, the measurements of STT values in the CAF combined with CTG or with porcine‐derived acellular dermal collagen matrix treatments were consistently greater than that in the CAF and CAF/HA groups when compared in the same design of our previous studies (Shirakata et al, 2016, 2019). These results also indicate that CTG or connective tissue alternatives may increase and maintain the volume of soft tissue in root coverage of multiple gingival recessions especially in thin biotype (Schlee & Esposito, 2011; Garces‐McIntyre et al, 2017; Stähli et al 2020).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The amounts of STT in the CAF/HA group were comparable to that in the CAF group, without statistically significant differences. On the other hand, the measurements of STT values in the CAF combined with CTG or with porcine‐derived acellular dermal collagen matrix treatments were consistently greater than that in the CAF and CAF/HA groups when compared in the same design of our previous studies (Shirakata et al, 2016, 2019). These results also indicate that CTG or connective tissue alternatives may increase and maintain the volume of soft tissue in root coverage of multiple gingival recessions especially in thin biotype (Schlee & Esposito, 2011; Garces‐McIntyre et al, 2017; Stähli et al 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Negative values were assigned to these measurements. If the gingival margin was located at the level of the coronal notch or coronal to this notch, a “0” value was applied (Casati et al 2000; Shirakata et al, 2019). (b) Epithelial length (EL): distance between the apical extent of junctional epithelium and the coronal notch when the gingival margin was coronal to the coronal notch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that application of EMD resulted in re-formation of root cementum, periodontal ligament, and alveolar bone, whereas treatment with SCTG led to long junctional epithelium establishment and even root resorption [13,14]. Moreover, EMD was found to play a key role in wound healing-promoting angiogenesis, revascularization, and soft-tissue regeneration [15], as well as enhanced collagen synthesis and the expression of transforming growth factor (TGF) β1 and TGF β2, vascular endothelial growth factor (vEGF), interleukin (IL)-1β, matrix metalloproteinase (MMP)-1, versican, and fibronectin [16]. Quite recently, Shirakata et al [17] reported significantly higher improvements in clinical parameters and greater complete periodontal regeneration in single gingival recession treated with coronally advanced flap and SCTG combined with EMD compared with defects treated without EMD in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies on recession defects using EMD combined with CAF [ 57 ], CTG [ 58 , 59 ] barrier membranes [ 60 , 61 ] revealed tissue formation essential for periodontal regeneration including cementum, PDL fibers and alveolar bone. An RCT using CAF plus EMD showed that it is a predictable therapeutic modality for gingival recession defects, easy to implement, low morbidity and a significant increase in the RC percentage, change in KTW and CAL [ 62 ].…”
Section: Discussionmentioning
confidence: 99%